The Influence of Regional Original Income, Special Allocation Funds, General Allocation Funds and Revenue Sharing Funds on Capital Expenditures in Regencies and Cities in North Maluku Province in 2017-2024 - Mulyaningsih, Eka; Hormati , Asrudin; Kusumaningrum, Sheila (Yayasan Riset dan Pengembangan Intelektual, 2025)
The purpose of this study is to identify the effect of Local Revenue, Special Allocation Fund, General Allocation Fund and Revenue Sharing Fund on Capital Expenditure in Regencies and Cities in North Maluku Province in 2017-2024. The data of this study are secondary data obtained from the Directorate General of Fiscal Balance. The data collection method uses statistical tests, which means that the entire population is used as a sample. The number of samples studied in this study was 80 samples. The research instrument used was multiple linear regression test using Eviews. The results of the study showed that Local Revenue and General Allocation Fund had a positive and significant effect on Capital Expenditure. While General Allocation Fund and Revenue Sharing Fund did not affect Capital Expenditure